A blindsnake that decapitates its termite prey. (7th July 2015) - Mizuno, T.; Kojima, Y.
Abstract: Almost all snakes swallow their prey whole. However, a few species are known as exceptions. Two species of Asian crab‐eating snakes tear off crab legs and ingest them one at a time to eat prey that is otherwise too large. Two species of leptotyphlopid blindsnakes break off the head of termites or suck abdominal contents of termites, discarding remains of termites. Here, we show that a typhlopid blindsnake I ndotyphlops braminus decapitates its termite prey and consumes only the thorax and abdomen. In our feeding trials, I . braminus decapitated a median of 47% of termites they eat, while swallowing the remaining termites whole. Decapitation did not affect ingestion speed, and therefore, it is unlikely that decapitation assists for fast ingestion. Ingested termite heads often remain undigested in the feces, implying that the decapitation functions to remove an indigestible part of termites. Decapitation might also be related to circumvention of chemical defenses of termites because termite heads often contain toxic compounds. These observations showed unusual feeding behavior used by a basal snake, which could be associated with removal of indigestible and/or toxic parts of prey items.